2021
DOI: 10.3390/antiox10111710
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Ameliorates the Cd-Induced Anxiety-like Behavior in Mice by Regulating Oxidative Stress and Neuro-Inflammatory Proteins in the Prefrontal Cortex Region of the Brain

Abstract: Age-related neurodegenerative diseases and vascular dementia are major challenges to the modern health care system. Most neurodegenerative diseases are associated with impaired spatial working memory and anxiety-like behavior. Thus, it is important to understand the underlying cellular mechanisms of neurodegenerative diseases in different regions of the brain to develop an effective therapeutic approach. In our previous research paper, we have reported the ameliorative effect of curcumin in Cd-induced hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…For instance, increased exposure to Cd was shown that caused memory damage by affecting antioxidant enzymes in the brain tissue of newborn pups 67 . All the above studies indicate that reduced antioxidant capacity following cadmium exposure gives rise to serious structure damage and all kinds of dysfunction of the central nervous system 68–70 . As expected, we pretreated SH‐SY5Y cells with NAC, which is known as an antioxidant, 71,72 the result showed it was significantly alleviated Cd‐induced upregulation of p‐PERK protein.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For instance, increased exposure to Cd was shown that caused memory damage by affecting antioxidant enzymes in the brain tissue of newborn pups 67 . All the above studies indicate that reduced antioxidant capacity following cadmium exposure gives rise to serious structure damage and all kinds of dysfunction of the central nervous system 68–70 . As expected, we pretreated SH‐SY5Y cells with NAC, which is known as an antioxidant, 71,72 the result showed it was significantly alleviated Cd‐induced upregulation of p‐PERK protein.…”
Section: Discussionmentioning
confidence: 60%
“…(n = 3). (*p < .05; **p < .01; ***p < .001 compared with the control group; # p < .05; ## p < .01; ### p < .001 compared with the CdCl 2 group).structure damage and all kinds of dysfunction of the central nervous system [68][69][70]. As expected, we pretreated SH-SY5Y cells with NAC, which is known as an antioxidant,71,72 the result showed it was significantly alleviated Cd-induced upregulation of p-PERK protein.…”
mentioning
confidence: 93%
“…Because oxidative damage and inflammation are involved in neuropsychiatric disorders (Gelders et al., 2018 ; McManus & Heneka, 2017 ; Yaribeygi et al., 2018 ), antioxidants may be able to reduce the symptoms of such disorders. For example, curcumin ameliorates spatial working memory and anxiety‐like behavior through reduction of prefrontal cortex neuroinflammation and oxidative stress (Namgyal et al., 2021 ). In addition, it has been reported that gallic acid improves anxiety and locomotor activity and memory deficits induced by chronic stress (Dhingra et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This also could be because antioxidants with low dose would show antioxidant activity in vivo, but they with high dose would exhibit pro-oxidative activity in vivo [ 132 , 133 , 134 ]. Additionally, in a cadmium-exposed mouse model, curcumin decreased anxiety-like behaviors by promoting the production of viable prefrontal cortex neuronal cells, and suppressing neuroinflammation in prefrontal cortex [ 135 ]. In addition, the intermediate dose of blackberry juice decreased anxiety-like behaviors, and the anxiolytic mechanism might be similar to diazepam [ 136 ].…”
Section: Anxietymentioning
confidence: 99%